Agroclimatic Zoning to species of Eucalyptus Genus in the State of Southern Mato Grosso do Sul (Research, Society and Development, 2020)
The Eucalyptus culture is of economic importance for Brazil, mainly for the state of Mato Grosso do Sul, where it has 16% of planted areas. The current search for quality and productivity in eucalyptus culture must go through the delimitation of areas that are agroclimatically suitable for cultivation. In this sense, agroclimatic zoning was carried out for the cultivation of Eucalyptus camaldulensis, Eucalyptus grandis, Eucalyptus urograndis, Eucalyptus urophyla, Corymbia citriodora for the state of Mato Grosso do Sul, using geoprocessing techniques. 97 pluviometric stations and 15 meteorological stations from the state and surrounding regions were used to specialize precipitation, temperature and water deficit and then reclassify them for the generation of agroclimatic zoning. According to the results obtained, the state has areas with agroclimatic aptitude for all species of Eucalyptus, and the species E. camaldulensis presents the largest area of ​​aptitude when compared to the others, and can be cultivated in 64.5% of the state . For the species E. urophylla and E. urograndis, the areas suitable for their implantation are similar, however, the area with aptitude for E. urophylla is more comprehensive, as it is possible to cultivate these species at higher temperatures and with greater water deficit . E. grandis and C. citriodora have smaller areas of fitness mainly because they are demanding at lower temperatures.